Ambivalence Predicts Symptomatology in Cognitive-Behavioral and Narrative Therapies: An Exploratory Study - Braga, Cátia; Ribeiro, António P.; Sousa, Inês; Gonçalves, Miguel M. (Frontiers in Psychology, 2019)
The identification of poor outcome predictors is essential if we are to prevent therapeutic failure. Ambivalence - defined as the conflict between two opposed positions of the self: one favoring change and another one favoring problematic stability – has been consistently associated with poor outcomes. However, the precise relationship between ambivalence and clients´ symptomatology remains unclear. Objective: This study aims at assessing ambivalence´s power to predict symptomatology, using a longitudinal design. Methods: The complete 305 sessions of 16 narrative and cognitive-behavioral cases have been analyzed with the Ambivalence Coding System and outcome measures have been used for each session. Results: Ambivalence emerged as a significant predictor of subsequent symptomatology suggesting that ambivalence is not only related to treatment outcomes, but that it represents a strong predictor of subsequent symptomatology. Discussion: The implications of ambivalence´s power to predict outcomes for research and clinical practice are discussed.